Production of Bacterial Cellulose by Acetobacter tropicalis Isolated from Decaying Apple Waste - Kaur, Lakhvinder; Shah, Shachi (Asian Journal of Chemistry, 2022)
Fruits and vegetables have the highest wastage rates of 45% of any food. One of the recent research areas is food waste valorization as a potential alternative to the disposal of a wide range of organic waste using microorganisms as one of the strategies known as microbial valorization. Bacterial cellulose is best known microbial valorization product because of its low cost, environmentally friendly nature, renewability, nanoscale dimensions, biocompatibility and extremely high hydrophilicity. Therefore, present study focuses on the isolation, characterization and identification of cellulose producing bacteria from decaying apple waste. Cellulose producers were isolated from decaying apple waste. The bacterial isolates obtained were identified through the morphological biochemical, physiological and molecular identification. The bacterial isolates exhibited potential remediation options to biovalorize decaying fruit waste by producing value added products as well as in safe disposal of waste.